47.4: Study on the flicker shift in FFS TFT‐LCD Mode. (4th October 2019) - Shi, Chengying; Cai, Min; Fu, Jiongliang; Wang, Yiming; Qin, Dandan; Xia, Zhiqiang
Abstract : Based on FFS TFT‐LCD panel, flicker shift with different cell materials was investigated, including lighting effect on the shift value with backlight on and off. Negative LC shifts much smaller than positive LC, even after reliability test. High resistance PI A shows a better result less than 1dB, while the low resistance PI B shift about 8dB, including introduce a DC voltage when lighting is on. However this DC can be compensated mainly by DC caused by the flexoelectric effect, which proposed a method to reduce flicker shift value with PI B. The DC caused by the flexoelectric effect is further improved by the asymmetric voltage‐transmittance (VT) curve. These studies can give the guidance for improving the flicker shift phenomenon in FFS mode.